Achieving ultra-high strength and ductility in equiatomic CrCoNi with partially recrystallized microstructures. (15th February 2019) - Slone, C.E.; Miao, J.; George, E.P.; Mills, M.J.
Abstract: Despite having otherwise outstanding mechanical properties, many single-phase medium and high entropy alloys are limited by modest yield strengths. Although grain refinement offers one opportunity for additional strengthening, it requires significant and undesirable compromises to ductility. This work therefore explores an alternative, simple processing route to achieve strength by cold-rolling and annealing an equiatomic CrCoNi alloy to produce heterogeneous, partially recrystallized microstructures. Tensile tests reveal that our approach dramatically increases the yield strength (to ∼1100 MPa) while retaining good ductility (total elongation ∼23%) in the single-phase CrCoNi alloy. Scanning and transmission electron microscopy indicate that the strengthening is due to the non-recrystallized grains retaining their deformation-induced twins and very high dislocation densities. Load-unload-reload tests and grain-scale digital image correlation are also used to study the accumulation of plastic deformation in our highly heterogeneous microstructures. Graphical abstract: Image 1